ChatGPT’s Impact on Environmental Literacy through Dahl’s Children’s Literature in Islamic Primary School - Oktaviansyah, Muhammad Eko; Safitri, Olvie Monika (PT Ilmu Inovasi Nusantara, 2024)
This study explores the impact of using ChatGPT on environmental literacy among fifth-grade students at MIN 1 Bengkulu City, Indonesia. This research employs a mixed-methods approach and analyzes four works by Roald Dahl—Giraffe and the Pelly and Me (2007), James and the Giant Peach (2007), Fantastic Mr. Fox (2007), and Danny the Champion of the World (2009). The environmental themes in these works are analyzed through the critical framework of Matthew Arnold, which highlights the moral relationship between humans and nature. The study involves two groups: an experimental group using ChatGPT to explore environmental themes, and a control group utilizing traditional teaching methods. Environmental literacy is measured through pre-test and post-test assessments, supported by student questionnaires and teacher interviews. Quantitative findings show a significant improvement in the experimental group (p < 0.05), indicating that the use of ChatGPT enhances students’ understanding of ecological issues. Qualitative data reveals higher student engagement and a positive perception of ChatGPT as a learning tool. From an Arnoldian perspective, these narratives prove effective in cultivating environmental appreciation by emphasizing the moral connection between humans and nature. Overall, this study demonstrates how AI-based tools, combined with children’s literature, can enrich the learning experience and promote sustainable thinking among elementary school students.